Desenvolvimento de escala para mensurar o desempenho social empresarial: um estudo com as mil maiores empresas do Brasil - Pereira, Marcello Monteiro (2018)
Social Responsibility is a widespread theme in academia, but there is still a theoretical gap related to quantitative empirical research. This thesis has as a research problem to verify if the dimensions of the concept of Social Performance of the literature (principles, processes and results) can be identified and validated by empirical research. The overall goal is to develop a scale to measure the CSP construct. In order to reach the proposed objectives and to respond to the research problem, the quantitative research methodology was used, more specifically the survey, performed with 253 executives of the thousand largest companies in Brazil according to the Valor Econômico ranking. As the main research result, it is possible to affirm that the dimensions of CSP can be identified and measured in empirical studies.